Desmoplastic infantile ganglioglioma: A case report and review of literature - Jalal, Jalal A.; Hama, Kadamkher R.; Al- Khurri, Luay E. (Zanco Journal of Medical Sciences (ZJMS), 2018)
Background and objective: Desmoplastic infantile gangliogliomas are rare low grade supratentorial masses that are seen in the pediatric age group. Typically, they involve the superficial cerebral cortex and leptomeninges. Despite the large size of these lesions and some worrisome histological and radiological features, prognosis is generally favorable after gross total resection. To our knowledge, out of about one hundred cases reported worldwide, this is the first Desmoplastic infantile ganglioglioma reported in Kurdistan region-Iraq. Case presentation: We report a case of Desmoplastic infantile ganglioglioma in a 2-month-old male infant, Computed tomography and magnetic resonance imaging revealed a supratentorial mixed cystic and solid temporal tumor. Near total surgical removal was done. Histopathology revealed features of desmoplastic infantile ganglioglioma, with marked desmoplastic component, glial and neuronal elements. Immunohistochemistry showed positive staining for glial fibrillary acidic protein with areas of synaptophysin positivity. Conclusion: The diagnosis of Desmoplastic infantile ganglioglioma should be considered in differential diagnosis of tumors with a cystic component and an aggressive appearance.